The Use Of The “Sipenda Cantik” Communication Technology As A Tool For Taxpayer Awareness - Lia Sukmawati; Siti Khumayah; Aghnia Dian Lestari (Jurnal Polisci, 2026)
“Community-Based Local Tax Data Collection Information System: Accurate and Convenient through Creative Technology” known as the “SIPENDA CANTIK” application is a digital innovation for local tax data collection, information dissemination, and payments developed by the Regional Revenue Management Agency (BAPPENDA) of Kuningan Regency. Increasing public awareness and compliance with tax obligations is the primary objective of this application’s creation. The objective of this study is to analyze public tax compliance awareness through the SIPENDA CANTIK communication platform and to identify supporting factors in its usage process. Through interviews and observations, this study employs a descriptive qualitative method. As the primary source of Local Original Revenue and an indicator of local government capacity, local taxes play a crucial role; thus, the use of the SIPENDA CANTIK digital innovation can significantly support this process. This study found that communication strategies have a significant impact on the effectiveness of SIPENDA CANTIK.